The Many Faces of IpaB - Picking, Wendy L.; Picking, William D. (Frontiers in Cellular and Infection Microbiology, 2016)
The type III secretion system (T3SS) is Shigella's most important virulence factor. The T3SS apparatus (T3SA) is comprised of an envelope-spanning basal body and an external needle topped by a tip complex protein called IpaD. This nanomachine is used to deliver effector proteins into host cells to promote pathogen entry. A key component of the matured T3SS needle tip complex is the translocator protein IpaB. IpaB can exist in multiple states when prepared as a recombinant protein, however, it has also been described as having additional roles in Shigella pathogenesis. This mini-review will briefly describe some of the features of IpaB as a T3SS needle tip protein, as a pore-forming translocator protein and as an effector protein. Reflection on the potential importance of the different in vitro states of IpaB on its function and importance in serotype-independent vaccines is also provided.